Isolation of Microalgae from Mediterranean Seawater and Production of Lipids in the Cultivated Species - Imane Haoujar; Francesco Cacciola; Manuel Manchado; Jamal Abrini; Mohammed Haoujar; Kamal Chebbaki; Marianna Oteri; Francesca Rigano; Domenica Mangraviti; Luigi Mondello; Adil Essafi; Hicham Chairi; et al. (Foods, 2020)
Isolation and identification of novel microalgae strains with high lipid productivity is one of the most important research topics to have emerged recently. However, practical production processes will probably require the use of local strains adapted to commanding climatic conditions. The present manuscript describes the isolation of 96 microalgae strains from seawater located in Bay M’diq, Morocco. Four strains were identified using the 18S rDNA and morphological identification through microscopic examination. The biomass and lipid productivity were compared and showed good results for Nannochloris sp. (15.93 mg/L/day). The lipid content in the four species, namely Nannochloropsis gaditana, Nannochloris sp., Phaedactylum tricornutum and Tetraselmis suecica, was carried out by high performance liquid chromatography coupled to mass spectrometry (HPLC-MS ) highlighting the identification of up to 77 compounds.